PVTOL maneuvers guided by a high-level nonlinear controller applied to a rotorcraft machine - Brandãoa, Alexandre Santos (2014)
This work proposes a nonlinear controller, based on the Theory of Lyapunov, to stabilize a quadrotor when accomplishing positioning and trajectory tracking tasks restricted to a vertical plane. The maneuvers addressed here are commonly accomplished by PVTOL (Planar Vertical Take-off and Landing) vehicles due to the flight constraints: movement restricted to the Z-axis or to the XZ/YZ planes. The contributions of the paper are the nonlinear controller itself, the proof of stability of the equilibrium of the closed-loop system, and the proposal of an analytical solution to saturate the control signals to prevent the saturation of the physical actuators. Experimental results are also presented, which validate the proposed controller.